A aprendizagem de inglês mediada por jogos eletrônicos do tipo MMORPG - Soares, Wilka Catarina da Silva (2013)
Massively Multiplayer Online Role-Playing Games (MMORPGs) are role-playing games that, through the Internet, can integrate thousands of players interacting at the same time in at least one virtual world. This way, these games can provide, further than fun, a greater familiarity with the additional language and opportunity to improve the linguistic proficiency in a real context. Hence, what is proposed in this study is extended knowledge about the learning of an additional language mediated by MMORPGs for teachers to know how, if relevant, to present, use or encourage this practice to their students. Based on this major purpose, we seek to answer the following research questions: (a) what distinguishes the learning profile of the gamers and non-gamers; (b) if MMORPGs can, through a hybrid and systematic approach, assist the development of proficiency of the additional language and (c) what the think-aloud protocols show about the learning mediated by the MMORPG Allods Online. Following an experimental method (NUNAN, 1997), 16 students of the curricular component Reading and Writing Practices in English Language have comprised the control group and 17 students of the same class formed the experimental group and were submitted to a pre and post-test adapted from the Key English Test (KET) by the Cambridge University (2008). The tests were conducted before and after a period of 5 weeks of 3 hours of practice with Allods Online a week (experimental group), and classes of the curricular component (both groups). A quantitative analysis of the questionnaires about the exposure to English profiles of the participants, a quantitative analysis of the tests scores and a qualitative analysis of the thinkaloud protocols collected during the experiment were conducted based on the theories of (a) motivation (GARDNER, 1985, WILLIAMS & BURDEN, 1997, BROWN, 2007, HERCULANO-HOUZEL, 2005); (b) active learning (GASS, 1997, GEE, 2008, MATTAR, 2010); (c) interaction and collaborative learning (KRASHEN, 1991, GASS, 1997, VYGOTSKY, 1978); (d) situated learning (DAMASIO, 1994; 1999; 2003, BROWN, 2007, GEE, 2003) and (e), tangential learning (PORTNOW, 2008; MATTAR, 2010). The results indicate that the participants of the experimental group (gamers) seem to be more engaged in tangential English learning activities, such as playing games, listening to music in English, communicating with foreigners and reading in English. We also deduced that the period of experiment possibly generated positive results on the gamers proficiency scores, mainly in the parts related to orthographic development, reading and comprehension, writing with focus on content and orthographic accuracy. Lastly, the think-aloud protocols presented evidences that the gamers have engaged in active English language learning, they have interacted in English with other players, and learned linguistic aspects through the experience with the MMORPG Allods Online